Large Arrays and Properties of 3‐Terminal Graphene Nanoelectromechanical Switches. (12th December 2013) - Liu, Xinghui; Suk, Ji Won; Boddeti, Narasimha G.; Cantley, Lauren; Wang, Luda; Gray, Jason M.; Hall, Harris J.; Bright, Victor M.; Rogers, Charles T.; Dunn, Martin L.; Ruoff, Rodney S.; Bunch, J. Scott
<x xml:space="preserve">Abstract</x> Large arrays of 3‐terminal nanoelectromechanical graphene switches are fabricated. The switch is designed with a novel geometry that leads to low actuation voltages and improved mechanical integrity, while reducing adhesion forces, which improves the reliability of the switch. A finite element model including non‐linear electromechanics is used to simulate the switching behavior and to deduce a scaling relation between the switching voltage and device dimensions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>